Bi(OTf)3‐Mediated (4+1) Annulation of α‐Sulfonyl o‐Hydroxyacetophenones with α‐Hydroxy Arylketones to Access Sulfonyl 2‐Aroylbenzofurans - Chang, Meng‐Yang; Chen, Kuan‐Ting (Advanced synthesis & catalysis, 2021)
In this paper, a high‐yield, facile route for the scalable synthesis of sulfonyl 2‐aroylbenzofurans via a Bi(OTf)3‐mediated intermolecular double cyclocondensation of α‐sulfonyl o‐hydroxyacetophenones with substituted α‐hydroxy arylketones under mild open‐vessel reaction conditions is described. In the overall reaction, water is generated as the only byproduct. Various metal triflate‐promoted reactions and conditions are investigated for the efficient one‐pot (4+1) annulation reaction.